Pengembangan UMK Melalui Pendampingan Penambahan Sertifikasi Halal Kode Fasilitasi BPJPH SEHATI 2025 - Masdarullia Aliyah Agustin; Nurjanti Takarini (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
The community service activity in Jemur Wonosari Village aims to provide education and assistance in terms of adding halal certification applications for the BPJPH SEHATI 2025 facility code to Micro and Small Enterprises (MSEs). Many Micro and Small Enterprises (MSEs) have not registered halal certification for all their product categories, causing obstacles for business actors in entering the modern market. Therefore, the main objective of this community service activity is to assist Micro and Small Enterprises (MSEs) to be able to add halal labels to all product categories they have. In addition, the purpose of adding halal certification applications is as a form of compliance of Micro and Small Enterprises (MSEs) to government regulations. This mentoring program is carried out by means of assistance in registering new halal certification applications through the Halal Information System (SIHALAL). The method used by the author is a qualitative method with a descriptive approach where the aim is to understand in depth the business legality problems experienced by Micro and Small Enterprises (MSEs) in the Jemur Wonosari Village area, especially in adding halal certification applications. The results of this community service activity were that four Micro and Small Enterprises (MSMEs) successfully added halal labels to other product categories. Furthermore, these entrepreneurs learned the importance of applying for halal certification for long-term business development and advancement. This activity significantly contributed to the development and advancement of Micro and Small Enterprises (MSMEs) in Jemur Wonosari Village.